Pengaruh Pemecahan Saham (Stock Split) pada Return Saham Dengan Inflasi sebagai Variabel Moderasi - Wira Pradipta, I Kadek Agus; Jati, Ketut (E-Jurnal Akuntansi; Vol 21 No 2 (2017), 2017)
Stock split is an activity undertaken by a Go Public company to raise the number of shares where its activity is usually done when the stock price is too high that will reduce the ability of investors to buy it. Stock split is done to increase profit and return. Splitting stocks in vain if acquired economic turmoil. Companies and investors need to consider the factors that affect. The purpose of this study is to obtain evidence of stock variables. This research was conducted at companies listed on Indonesia Stock Exchange 2011-2015. The number of samples of 41 companies with a total of 41 observations. The method used is nonprobability sampling technique with purposive sampling technique. Data collection is based on documentary techniques. Multiple regression analysis (MRA). Split the stock proxy with the stock split, and again proxied with return, and inflation is proxied with inflation. Based on the discussion of the results of research that has been done can be concluded, inflation has a significant effect on the relationship stocks. (Stock split) on stock return and a positive impact on the process that occurs between stocks. Keywords : Stock Split, Inflation, Stock Return, Return